Traditional Chinese medicine in cardiovascular drug discovery. (October 2020) - Leung, Elaine Lai-Han; Xu, Suowen
Abstract: In this virtual special issue entitled "Traditional Chinese Medicine in Cardiovascular Drug Discovery", a collection of 18 basic research, clinical research and review articles was published to highlight the therapeutic potential of traditional Chinese medicine (TCM) and their bioactive components in treating atherosclerosis, coronary artery disease, ischemic cardiomyopathy, heart failure and beyond.